2001
DOI: 10.1186/1471-2199-2-14
|View full text |Cite
|
Sign up to set email alerts
|

A human RNA polymerase II subunit is encoded by a recently generated multigene family

Abstract: Background: The sequences encoding the yeast RNA polymerase II (RPB) subunits are single copy genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Here, we provide the first evidence about in vivo functional distinction between the previously discovered [20][21][22][23][24][25][26] distinct human isoforms of the hRPB11 (POLR2J) subunit of RNA polymerase II of Homo sapiens: The strength of the hRPB11-ATF4 interaction in corresponding transcription complexes appeared to be isoform-specific.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Here, we provide the first evidence about in vivo functional distinction between the previously discovered [20][21][22][23][24][25][26] distinct human isoforms of the hRPB11 (POLR2J) subunit of RNA polymerase II of Homo sapiens: The strength of the hRPB11-ATF4 interaction in corresponding transcription complexes appeared to be isoform-specific.…”
Section: Introductionmentioning
confidence: 74%
“…Previously, we have shown that, in drastic difference with all other species, small indispensable subunit Rpb11 of RNA polymerase II is encoded in Homo sapiens by four different genes located on chromosome 7 [20,21]. One gene, POLR2J1 (~5.5 kb long), is orthologous to the corresponding rpb11 genes in other species and encodes the usual (trivial), main isoform of hRPB11 (POLR2J) subunit called hRPB11a (117 aa long) which, as judged by its evolutionary history, is the subject of strong purifying selection because is strictly conserved in all warm-blooded animals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations